Implementation of Librarian Knowledge Management in a Developing Regional Library: A Wiig Model-Based Analysis at Pakpak Bharat Regional Library - Ela Febrita Tinendung; Abdi Mubarak Syam (Ali Institute of Research and Publication, 2026)
This study examines the implementation of librarian knowledge management at the Pakpak Bharat Regional Library using the Wiig Model. It aims to describe how librarians build, store, share, and use knowledge in library activities, as well as to identify supporting and inhibiting factors in its implementation. This study employed an exploratory qualitative method. Data were collected through interviews, observations, and documentation, and were analyzed based on the four stages of the Wiig Model: building knowledge, holding knowledge, pooling knowledge, and using knowledge. The findings indicate that knowledge management has begun to be implemented through work experience, leadership guidance, training, self-directed learning, standard operating procedures, archives, INLISLite, Bindella Pakpak, staff discussions, and user services. However, its implementation is not yet fully structured due to limited human resources, the absence of librarians with a library science background, irregular training, and limited documentation of work experiences. This study provides an empirical overview of early knowledge management practices among librarians in a developing regional library.